Fishbone Strategy in Teaching Writing Recount Text for The Eighth Grade Students of SMP N 2 Habinsaran - Lisviani Pardede; Puan Suri Mira Annisa (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This study aimed to (1) describe the implementation strategy in teaching writing recount text (2) to analyze the barriers faced by the teacher in implementing fishbone strategy in teaching writing recount text. The participants of this research were 20 students of tenth grade students of SMP Negeri 2 Habinsaran. The type of research method in this study is descriptive qualitative research. The data collection instruments used in this study were observation, interview, and documentation. The teacher was applied the fishbone strategy starting from the Preparation stage, Pre Teaching Stage, Whilst Teaching Stage to the final stage of Post Teaching Stage. Each stage of the teacher performed well and the students' actions when applying the fishbone strategy in writing recount texts were also good. But in implementing the strategy, the teacher has barriers dealing with student deficiencies. It was revealed when the researcher interviewed the teacher after the teaching and learning process was completed.Keywords: Fishbone Strategy, Writing, Recount Text